The Implementation of Reflective Teaching through Students’ Feedback in Teaching English at MTsS YMPI Rappang - Ayu S; Syarifuddin Dollah; Chairil Anwar Korompot (Journal of Excellence in English Language Education, 2022)
This study aimed to find out the implementation of reflective teaching through student’s feedback in teaching English at MTsS YMPI Rappang and find out the obstacles that teachers at MTsS YMPI Rappang face in doing reflective teaching through students’ feedback. This research includes qualitative research with descriptive qualitative. The subject of the research is an English teacher of MTsS YMPI Rappang that implements reflective teaching through student’s feedback. This study uses purposive sampling. The data was collected through interview and observation. The data was collected by means of reduction, data display and draw a conclusion. Based on the finding of research, the researchers found that the teacher implemented reflective teaching through students’ feedback in 4 steps, namely data collection, data analysis, reflection, and plan for action. The obstacle that the teacher at MTsS YMPI Rappang faced in doing reflective teaching through students’ feedback is time because   he has to provide time to teaching in the school, teaching in his English course, and providing time as teacher guidance and counseling.